In vitro Effect of Harmine Alkaloid and Its N-Methyl Derivatives Against Toxoplasma gondii - Alomar, Maria L.; Yañuk, Juan G.; Angel, Sergio O.; Gonzalez, M. Micaela; Cabrerizo, Franco M. (Frontiers in Microbiology, 2021)
Toxoplasmosis is one of the most prevalent and neglected zoonotic global diseases caused by Toxoplasma gondii. The current pharmacological treatments show clinical limitations and, therefore, the search for new drugs is an urgent need in order to eradicate this infection. Due to their intrinsic biological activities, β-carboline (βC) alkaloids might represent a good alternative that deserve further investigations. In this context, the in vitro anti-Toxoplasma gondii activity of three βCs, harmine (1), 2-methyl-harmimium (2) and 9-methyl-harmine (3) was evaluated herein. Briefly, the three alkaloids exerted direct effects on the parasite invasion and/or replication capability. Replication rates of intracellular treated tachyzoites were also affected in a dose-dependent manner, at non-cytotoxic concentrations for host cells. Additionally, cell cycle analysis revealed that both methyl-derivatives, 2 and 3, induce parasites arrest in S/M phases. Compound 3 showed the highest irreversible parasite growth inhibition, with a half maximal inhibitory concentration (IC50) value of 1.8 ± 0.2 µM and a selectivity index (SI) of 17.2 at 4 days post-infection. Due to high replication rates, tachyzoites are frequently subject to DNA double strand breaks (DSB). This highly toxic lesion triggers a series of DNA damage response reactions, starting with a kinase cascade that phosphorylates a large number of substrates, including the histone H2A.X to lead the early DSB marker γH2A.X. Western blot studies showed that basal expression of γH2A.X was reduced in the presence of 3. Interestingly, the typical increase in γH2A.X levels produced by camptothecin (CPT), a drug that generates DSB, was not observed when CPT was co-administered with 3. These findings suggest that 3 might disrupt Toxoplasma DNA damage response.